Hybridization effects on the fatigue properties of novel core‐in‐sheath‐type carbon/glass hybrid thermoplastic composite rods. Issue 12 (26th August 2022) - Oguma, Hiroyuki; Naito, Kimiyoshi
Abstract: In this study, novel core‐in‐sheath‐type carbon/glass hybrid thermoplastic composite rods with three different carbon/glass ratios were developed. Then, the fatigue behaviors of these rods and their influential factors were investigated. The hybridization of fibers and presence of voids strongly affected the stress dependency of their fatigue life; the hybrid rods with the highest volume fraction of carbon fibers and the lowest one of void showed the highest fatigue strength behavior. The fatigue behavior of the hybrid rods could be predicted via the rule of mixture by using fatigue test data from unidirectional carbon fiber‐ and glass‐fiber‐reinforced polymer laminated plates. The structure and dispersion degree of the hybrid rods allowed the prediction of their fatigue behavior based on their constituents with a simple parallel model. Highlights: Core‐in‐sheath carbon/glass hybrid thermoplastic composite rods were developed. The hybridization and voids strongly influenced the stress dependency of fatigue life. The fatigue behavior was predicted via the mixture rule with fatigue data of pure FRPs.